Association of Parental Stroke with Brain Injury and Cognitive Measures in Offspring – The Framingham Heart Study - Weinstein, Galit (2013)
BACKGROUND AND PURPOSE: Parental stroke has been related to an increased risk of stroke in the offspring. This study examines whether parental stroke is also associated with increased vascular brain injury and poorer cognitive performance among offspring free of clinical stroke. METHODS: Multivariable regression analyses were used to relate parental stroke to cross-sectional and change in brain magnetic resonance imaging measures and cognitive function among the offspring, with and without adjustment for vascular risk factors. RESULTS: Stroke- and dementia-free Framingham Offspring (n=1,297, age:61±9 years, 54% women) were studied. Parental stroke by age 65 years was associated with a higher baseline white matter hyperintensity volume (WMHV;β=0.17±0.08; p=0.027), and with lower visual memory performance (β =−0.80±0.34; p=0.017). During a 6 year follow-up, parental stroke was also associated with increase in WMHV (odds ratio [OR] = 1.87;95%CI:1.03–3.38) and decline in executive function (Trails B–A; OR=1.81;95%CI:1.06–3.09). The associations with WMHV and visual memory attenuated after additional adjustment for concomitant vascular risk factors. CONCLUSIONS: Parental stroke by age 65 years is associated with increased vascular brain injury and lower memory in offspring equivalent to 3 and 7 years of brain aging, respectively. This may be partly attributed to inheritance of vascular risk factors.